STRUKTUR MIRKOANATOMI HEPAR TIKUS (RATTUS NORVEGIGUS, L) YANG DIPERLAKUKAN DENGAN MINYAK HATI IKAN COD - Solang, Margaretha (Sainstek, 2008)
The aims of this research was to study the effects of cod liver oil on microanatomic structure of rats liver (Rattus norvegicus, L.). The present research used of Completely Randomized Design comprised of 25 Wistar males, randomly divided into five groups (A, B, C, D, and E). Group A was assigned as control, whereas B, C, D, and E were given cod liver oil with doses of 0,5, 1, 1,5, and 2 ml/b w/ day for 8 weeks, respectively. The parameters observed were microanatomic structure of rats liver (Rattus norvegicus, L.). The determination of liver for microanatomic preparation were done at the end of treatments. Qualitative data were analyzed descriptively. The research demonstrated that rats liver cells underwent plasmolyses, cloudy swelling degenerations, hydrophic degenerations, fatty degenerations and necroses (pycnoses and karyorrhexis).